INFLUENCE OF DIFFERENT LEVELS OF ENERGY AND PROTEIN ON CUMULATIVE FEED CONSUMPTION AND FEED CONVERSION RATIO OF BROILERS IN ENVIRONMENTALLY CONTROLLED HOUSING SYSTEM - K. Rajendran; K. Mani; P. Shamsudeen; V. Ramesh Saravana Kumar; A. Natarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Two hundred and eighty eight chicks were divided into nine groups and provided with diets with three different levels of energy in three periods (2850, 2950 and 3050 kcal/ kg in pre-starter diet, 2950, 3050 and 3150 kcal/kg in starter diet and 3050, 3150 and 3250 kcal/kg in finisher diet) and protein levels in three periods (21.5, 22.5 and 23.5% in pre- starter diet, 20.5, 21.5 and 22.5% in starter diet and 19, 20 and 21% in finisher diet) to commercial broilers for a period of five weeks to assess the production performance. Result of the experiment revealed that the energy and protein content of the diet had significantly influenced body weight, cumulative feed intake and feed conversion ratio in broilers.